Timber beds, protests and publics: conflicting meanings of the public interest on Devonshire Street, Sheffield. Issue 5 (1st September 2021) - Maidment, Christopher
Abstract : This paper discusses a case small in scale, but which raises questions around how different conceptions of what is in the public interest are reconciled in the English regulatory planning system. The case in question is the proposed redevelopment of three 1850s shops in Sheffield's Devonshire Quarter, traditionally home to independent retailers. The article illustrates how a small-scale planning application can generate national attention, through a range of misunderstandings, conflicting interests and a narrow definition of what constitutes knowledge in English planning. Particular attention is paid to how a different approach to decision making might have facilitated a compromise solution, through thinking about what is in the public interest at different scales. The core argument is around the need to address how public participation in planning processes can be based on more equitable use of knowledge. This leads to conclusions around how the system can better reconcile multiple interests.